Academic Writing: A Discipline or Disciplines? - I. M. Zashikhina (Высшее образование в России, 2021)
In the last five years, the discipline “Academic Writing” in one form or another has become part of the programs of many Russian universities. The goal of the discipline is the achievement of academic literacy. Within the framework of state policy in education and the need to increase publication activity, the discipline should teach students, graduate students and researchers to write a scientific article in accordance with the requirements of highly rated journals. In Russian education, the model of teaching academic writing was adopted from Western educational discourse. Since the 2010s, university teachers introduce courses, focusing on the experience of Western colleagues and sharing the results achieved. Researchers of academic writing point out a number of problems in teaching students. It is noted that students experience difficulties in mastering the competencies of the course, and teachers are not satisfied with the results. A number of articles appear in the media discourse, the authors of which express doubts about the appropriateness of practice of academic writing borrowed from the Western educational space. Indeed, in Western educational institutions, the development of academic writing skills begins at school, and then an extensive standard program is implemented at universities, covering various subject and cross-subject areas, within which the discipline is taught. In Russia, university students are confronted with a new field of knowledge and find themselves in a whirlpool of new rules, abilities, skills, competencies that they have to master in a short period of study a far as at the undergraduate level. The Western academic writing program is hardly applicable to the realities of Russian education. This article attempts to find the reason for the difficulties in teaching the discipline of academic writing to Russian students. The results of the study on three different groups of students studying the discipline of academic writing are presented. As a way out of a problem situation, the author proposes to divide the discipline into three levels, each of which covers a number of educational competencies necessary to create a specific product within the framework of the academic text genre.